Collapse and Resumption of the Thermohaline Circulation during Deglaciation : Insights by Models of Different Complexity - Knorr, Gregor (Staats- und Universitätsbibliothek Hamburg Carl von Ossietzky, 2005)
The transition between the last glacial (cold) and our modern interglacial (warm) period occurred between about 20,000 and 10,000 years before present, as indicated by proxy data from ice core, ocean sediment and terrestrial records. These data display that deglacial warming over Antarctica preceded a rapid warming in Greenland by more than 1000 years. Furthermore, a series of abrupt climate shifts suggest that massive reorganizations in the thermohaline circulation (THC) and accompanying variations in northward heat transport within the Atlantic have been involved in deglacial climate change. As yet, studies of these phenomena have focused mostly on the North Atlantic region to explain the succession of abrupt climate events. This is because North Atlantic deepwater formation sites, a sensitive key player of the THC, and various sources of freshwater coexist in this realm that perturb the circulation during deglaciation. Using three-dimensional global models of the ocean and the atmosphere, as well as a conceptual model, THC changes have been analysed that arise in response to different deglacial warming and meltwater scenarios. The results show that gradual global and Southern Hemisphere warming during deglaciation leads to an abrupt resumption of a stalled THC, while Northern Hemisphere warming is not sufficient to trigger an augmentation in presence of reasonable meltwater fluxes to the North Atlantic. The rapid transition to an interglacial THC is linked to large-scale salinity advection of near surface waters from the South Atlantic/Indian Ocean and the tropics to the formation areas of North Atlantic deep water, as well as heat release from the sub-surface North Atlantic. This THC transition can be related to the onset of the Bølling/Allerød warm interval 14,700 years ago. The interglacial circulation mode is characterized by a strong insensitivity to deglacial meltwater pulses, but possesses a distinct bistability in the hysteresis curve for cumulative positive freshwater fluxes to the North Atlantic. ...